Study of antimicrobial activity of extracts of sea buctorn - Zhuravel, Iryna; Naumenko, Lyubov (Annals of Mechnikov’s Institute, 2023)
Introduction. To date, the widespread use of antibacterial drugs of synthetic origin has created the problem of resistance of infectious agents to antimicrobial drugs. An equally frequent consequence of the use of antibiotics is a disturbance in the balance of intestinal microbiota. The creation of new herbal medicines with antimicrobial action is relevant in solving these problems. Phytopreparations have a mild, complex therapeutic effect and can be used in the long-term treatment of diseases. The pharmacological effect of these drugs is caused by a complex of biologically active substances, in particular phenolic compounds. One of the promising sources of antimicrobial agents is sea buckthorn (Hippоphaë rhamnoides L.). Its raw materials contain phenolic substances, which creates grounds for the development of new medicinal substances. Extracts obtained from leaves, fruits, stems and roots of sea buckthorn were tested for antimicrobial activity by foreign scientists. Researchers from Pakistan obtained extracts from sea buckthorn fruits by the method of maceration with chloroform, petroleum ether, methanol and purified water. Antimicrobial properties were studied in relation to Staphylococcus aureus, Bacillus subtilis, Streptococcus pneumoniae, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumonia, the results of research showed that these microorganisms were sensitive to the action of the studied extracts. Polish scientists studied the antimicrobial effect of methanol, hexane, ethyl acetate, butanol and water extracts from sea buckthorn leaves, stems and roots. The obtained leaf extracts were active against Bacillus cereus, Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus phecalis, Escherichia coli, Salmonella typhi, Shigella dysenteriae, Streptococcus pneumoniae. Methanolic extracts from sea buckthorn roots and stems have shown antimicrobial properties against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Salmonella typhimurium, as well as Pichia jadinii and Candida albicans yeasts. The domestic antiviral drug Erebra, which contains a complex of tannins from sea buckthorn leaves, is present on the pharmaceutical market of Ukraine. In vitro, the drug also has a moderate antimicrobial effect against Staphylococcus aureus and Escherichia coli, Proteus vulgaris, Pseudomonas aeruginosa, Mycobacterium tuberculosis, Candida albicans, Microsporum canis. We obtained dry and liquid ethanolic extracts from the leaves, bark and fruits of sea buckthorn by the method of vacuum filtration extraction and investigated their antimicrobial effect, while the extracts were extracted from the bark of the plant for the first time. The purpose of the study. To investigate the antibacterial and antifungal activity of the extracts obtained from herbal drugs of sea buckthorn. Materials and methods. To study the antimicrobial effect, liquid extracts from the leaves, bark and fruits of sea-buckthorn were obtained by the method of vacuum filtration extraction in the ratio of raw material extractant leaves 1:5, bark 1:5, fruits 1:10. The extraction was carried out at room temperature using a vacuum filtration extractor, and 70% ethanol was used as a solvent. Dry extracts were obtained by concentrating 70% ethanol extracts from sea buckthorn raw materials with subsequent drying in an oven at a temperature of 70°C.To study the antibacterial properties of extracts, standard test cultures of gram-positive and gram-negative bacteria belonging to different taxonomic groups were used: Staphylococcus aureus ATCC 25923, Essherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Bacillus subtilis ATCC6633, Proteus vulgaris ATCC 4636. Antifungal effect of extracts studied on the reference strain Candida albicans ATCC 885-653. The specified set of test strains is generally accepted for the primary determination of antimicrobial activity. All test cultures were obtained from the laboratory of medical microbiology with the Museum of Microorganisms of the State University "IMI named after I.I. Mechnikov National Academy of Sciences of Ukraine". Cultivation media were used according to the type of microorganisms in accordance with existing methodical developments and recommendations. Preparation of suspensions of microorganisms with a determined concentration of microbial cells (optical density) was carried out using a turbidity standard (0.5 units on the McFarland scale). We used a Densi-La-Meter device (manufactured by PLIVA-Lachema, Czech Republic; wavelength 540 nm). The suspension was prepared according to the instructions for the device and the information sheet on innovations in the health care system No. 163-2006 "Standardization of preparation of microbial suspensions", Kyiv. Synchronization of cultures was carried out with the help of low temperature (4oC). Determining the sensitivity of strains of microorganisms to antibacterial drugs was carried out by the method of wells on the Muller-Hinton medium ("HIMediaLaboratorlesPvt. Ltd India). The medium was prepared according to the manufacturer’s instructions. The sensitivity of fungi was determined on Saburo-dextrose agar medium. Determination of the sensitivity of the test substances was carried out on two layers of nutrient medium, which were poured into Petri dishes. The lower layer consisted of agar-agar (10 ml). 3-6 metal sterile cylinders with a diameter of 8 mm and a height of 10 mm were installed on it. The upper layer (14 ml of nutrient medium + 1 ml of microbial solution 0.5 units on the McFarland scale) was poured around the cylinders, which consisted of nutrient agar medium with the appropriate standard of daily culture of the microorganism. After solidification, the cylinders were removed with sterile tweezers and the test substance (0.3 ml) was introduced into the wells. The antibacterial activity of the test substances was assessed by the diameter of the zones of growth retardation. The results and their discussion. The results of the study of the antimicrobial activity of extracts from medicinal plant raw materials of sea buckthorn confirm that the studied phytoremedies have a pronounced antimicrobial effect, delay the growth of rod-shaped and cocci-like microflora, which are often the causative agents of hospital infections and secondary infections. Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Candida albicans were the most sensitive to the action of extracts, Proteus vulgaris was less sensitive. The most pronounced antimicrobial effect was noted in sea buckthorn leaf extract dry. It was bactericidal against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Proteus vulgaris and Candida albicans. Sea buckthorn bark dry extract was also no less effective. Its high bactericidal effect was manifested against five out of six investigated strains of microorganisms such as: Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Candida albicans. Sea buckthorn bark liquid extract showed a high level of antimicrobial activity against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Candida albicans, Proteus vulgaris was less sensitive to the action of this extract. The liquid extract of sea buckthorn leaves effectively inhibited the growth of Staphylococcus aureus, Escherichia coli, Bacillus subtilis and Candida albicans. Proteus vulgaris and Pseudomonas aeruginosa were less sensitive to its action. The liquid extract of sea buckthorn fruits significantly inhibited the growth of Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Candida albicans. Proteus vulgaris was less sensitive to its antimicrobial action. The dry extract of sea buckthorn fruits inhibited the growth of Staphylococcus aureus, Escherichia coli, Bacillus subtilis and Candida albicans well. Proteus vulgaris and Pseudomonas aeruginosa were less sensitive to its action. Conclusions: The antimicrobial activity of liquid and dry extracts of leaves, bark and fruits of sea buckthorn was studied. All studied extracts showed the ability to delay the growth of museum strains of microorganisms. Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Proteus vulgaris and Candida albicans were more sensitive to the action of sea buckthorn leaf dry extract and sea buckthorn bark dry extract. Among the microorganisms, Proteus vulgaris was the least sensitive to the action of all extracts. The investigated extracts of sea buckthorn are promising for the further creation of antimicrobial drugs based on them. Keywords: Hippоphaë rhamnoides L., antimicrobial activity, herbal drugs extracts.